Seasonal Changes of Growth, Immune Parameters and Liver Function in Wild Chinese Sturgeons Under Indoor Conditions: Implication for Artificial Rearing - Zheng, Yueping; Zhang, Yong; Xie, Zhe; Shin, Paul K. S.; Xu, Jianan; Fan, Houyong; Zhuang, Ping; Hu, Menghong; Wang, Youji (Frontiers in Physiology, 2022)
Seasonality has a significant effect on the physiology of fish, especially the effect of water temperature changes. In the present study, the growth, innate immune parameters and liver function indices of two rescued wild adult Chinese sturgeons under captive conditions were monitored for one year. The results showed that the total annual weight loss rate of the male was -4.58% and the total weight gain rate of the female was 24.12%, in which the weight of both individuals registered highly significant differences in summer, fall and winter (p<0.01). The male Chinese sturgeon also exhibited negative specific growth rates (-0.1 to -0.8%) during spring to fall, whereas positive specific growth rates, ranging from 0.03 to 0.11%, were recorded in the female. Seasonality also affected the innate immune parameters of the two Chinese sturgeons, in which leukocytes had been increasing since spring and C-reactive protein (CRP) content was significantly higher (p<0.05) in summer than fall in both individuals. The CRP level of the male Chinese sturgeon showed a significant increase from fall to winter (p<0.05), suggesting that it may have contracted infection or inflammation during this study period. With the analysis of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), transaminase (AST:ALT) ratio, alkaline phosphatase, albumin to globulin ratio and triglycerides, it was found that the liver function of the captive Chinese sturgeons was adversely affected along seasonal changes, with the highest degree of liver impairment in winter. In combining observations from growth performance and changes in innate immune and liver function parameters, the present findings deduced that the male Chinese sturgeon under study was more susceptible to seasonal changes than the female. For better indoor culture of adult Chinese sturgeons, monitoring of hematological parameters to detect early signs of inflammation and liver function abnormality should be conducted with routine veterinary care during prolonged captivity.